Conditional equations related to Drygas functional equations - Izadi, Sadegh; Jahedi, Sedigheh; Dehghanian, Mehdi (Annales Mathematicae Silesianae, 2025)
We determine the solutions of the conditional Drygas equation for functions f1 and f2 that satisfy (y2+y)f1(x) = (x2+x)f2(y) for all (x, y)∈ℝ2 under the additional conditions y = x2, or y = log(x), x > 0 or y = exp(x).